Universal scaling for disordered viscoelastic matter near the onset of rigidity - Liarte, Danilo B. [UNESP]; Thornton, Stephen J.; Schwen, Eric; Cohen, Itai; Chowdhury, Debanjan; Sethna, James P. (My University, 2022)
The onset of rigidity in interacting liquids, as they undergo a transition to a disordered solid, is associated with a rearrangement of the low-frequency vibrational spectrum. In this Letter, we derive scaling forms for the singular dynamical response of disordered viscoelastic networks near both jamming and rigidity percolation. Using effective-medium theory, we extract critical exponents, invariant scaling combinations, and analytical formulas for universal scaling functions near these transitions. Our scaling forms describe the behavior in space and time near the various onsets of rigidity, for rigid and floppy phases and the crossover region, including diverging length scales and timescales at the transitions.